Pengaruh Variasi Ukuran Daun Stevia dan Perbandingan Umpan pada Karakterisasi Produk Gula Cair Stevia - Jessica Jessica; Andy Chandra; Ign. Suharto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Sweetener is one of the food ingredients that consumed the most by humans. Sweeteners are classified into artificial and natural sweeteners. The excessive consumption of artificial sweeteners could lead into many diseases, such as obesity, cancer, etc. Moreover, the consumption of sweeteners increases significantly, but the sweeteners production in Indonesia still couldn’t balance the populations’ demand. Stevia contains glycosides which are up to 450 times sweeter than sucrose, but with low calories. The purpose of this research is to determine the effect of feed to solvent ratio (F:S) and Stevia leaves’ size variation to the extract’s concentration. This research was carried out using solid extraction method with an agitated tank. Stevia leaves were extracted with aquadest as the solvent at 60°C for 2 hours with feed to solvent ratio variations (1:100, 1:150, and 1:200) and leaves’ sizes variations (without mesh, -20+30 mesh, -40+60 mesh). The extracts then were analyzed using colorimeter and turbidimeter to determine the extracts’ concentrations, and also organoleptic testing. The results showed a tendency. From F:S=1:100, 1:150, and 1:200, the higher F:S, the lower the extract’s concentration obtained. On the other hand, the smaller the Stevia leaves, then the higher the extract’s concentration obtained.